Large Versus Small Opening Wedge High Tibial Osteotomies Performed With a Protective Wire Over the Lateral Hinge: Incidence of Lateral Hinge Fracture and Early Clinical Outcomes. Issue 3 (March 2023) - Koh, Don Thong Siang; Soong, Junwei; Yeo, William; Tan, Marcus Wei Ping; Teo, Shao Jin; Wilson, Adrian; Lee, Kong Hwee
Background: The incidence of lateral hinge fractures (LHFs) during medial opening wedge high tibial osteotomy (MOW-HTO) is unacceptably high, especially with distractions >10 mm. LHFs result in malunion, loss of correction, and recurrence of symptoms adversely affecting clinical outcomes. Purpose: (1) To investigate the incidence of LHF when a protective guide wire is utilized during MOW-HTO in small and large corrections and (2) to study the effect of correction size on early clinical outcomes. Study Design: Cohort study; Level of evidence, 3. Methods: A retrospective analysis was performed of 96 knees that underwent MOW-HTO between 2019 and 2020. A protective wire applied intraoperatively across the lateral hinge point before opening wedge distraction was performed for all patients. Patients were divided into 2 groups based on opening wedge sizes: group A (opening distraction <10 mm) and group B (opening distraction ≥10 mm). LHF and wound complications were recorded. Prospective Knee Score and Function Score (Knee Society), Oxford Knee Score, and Physical and Mental Component Summaries of the 36-Item Short Form Health Survey questionnaire were recorded preoperatively and at 6 months and 2 years after surgery. Results: Incidence of LHF was low in group A (n = 2; 6.1%) and group B (n = 3; 9.1%). A single case of intraoperative LHF was noted in each group, with each case resulting in a type 1 fracture. The incidence of postoperative fractures was comparable between groups (groups A vs B, n = 1 vs 2). At 6 months, clinical outcomes in group A were superior to those of group B (Knee Score, 85.7 ± 14.7 vs 73.1 ± 20.3, P = 0.028; Function Score, 73.5 ± 16.5 vs 63.1 ± 19.5, P = 0.047; Oxford Knee Score, 20.2 ± 4.7 vs 25.6 ± 8.5, P = 0.008; Physical Component Summary, 46.8 ± 8.1 vs 40.2 ± 10.9, P = 0.018). However, clinical outcomes were comparable at 2 years ( P > .05). Conclusion: A protective wire was associated with a low incidence of LHF, even in larger MOW-HTO corrections. Large corrections had poorer clinical outcomes as compared with small corrections at 6 months. However, clinical outcomes between groups were comparable at 2 years.